2017
DOI: 10.1016/j.stemcr.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of the Epithelial-to-Mesenchymal Transition Is Required for Embryonic Stem Cell Derivation

Abstract: SummaryPluripotent cells emanate from the inner cell mass (ICM) of the blastocyst and when cultivated under optimal conditions immortalize as embryonic stem cells (ESCs). The fundamental mechanism underlying ESC derivation has, however, remained elusive. Recently, we have devised a highly efficient approach for establishing ESCs, through inhibition of the MEK and TGF-β pathways. This regimen provides a platform for dissecting the molecular mechanism of ESC derivation. Via temporal gene expression analysis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Via temporal gene expression analysis, we revealed before the key genes involved in the ICM to ESC transition by blocking both the ERK1/2 and TGFβ signaling pathways. 30 Interestingly, our results depicted the upregulation of 233 well-known relevant pluripotency-related markers, such as Pou5f1 (Oct4), Zfp42(Rex1), Klf4, Ctnnb1 (β-Catenin), Sall4, Nanog, Klf2, Dppa3, Sox2, Esrrb, Utf1, Gbx2, and Nr5a2. In addition, blockage of the ERK and TGF-β pathways resulted in a high expression of epigenetic modifiers and DNA methylation-related genes such as Dnmt3b, Dnmt3l, Chd8, Mtss1, Suz12, Eed, Wdr3, and Mat2b in the transition from ICM to ESCs such as Dnmt3b, Dnmt3l, Chd8, Mtss1, Suz12, Eed, Wdr3, and Mat2b.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Via temporal gene expression analysis, we revealed before the key genes involved in the ICM to ESC transition by blocking both the ERK1/2 and TGFβ signaling pathways. 30 Interestingly, our results depicted the upregulation of 233 well-known relevant pluripotency-related markers, such as Pou5f1 (Oct4), Zfp42(Rex1), Klf4, Ctnnb1 (β-Catenin), Sall4, Nanog, Klf2, Dppa3, Sox2, Esrrb, Utf1, Gbx2, and Nr5a2. In addition, blockage of the ERK and TGF-β pathways resulted in a high expression of epigenetic modifiers and DNA methylation-related genes such as Dnmt3b, Dnmt3l, Chd8, Mtss1, Suz12, Eed, Wdr3, and Mat2b in the transition from ICM to ESCs such as Dnmt3b, Dnmt3l, Chd8, Mtss1, Suz12, Eed, Wdr3, and Mat2b.…”
Section: Discussionmentioning
confidence: 62%
“…Via temporal gene expression analysis, we revealed before the key genes involved in the ICM to ESC transition by blocking both the ERK1/2 and TGFβ signaling pathways . Interestingly, our results depicted the upregulation of 233 well‐known relevant pluripotency‐related markers, such as Pou5f1 ( Oct4 ), Zfp42 ( Rex1 ), Klf4 , Ctnnb1 (β ‐Catenin ), Sall4 , Nanog , Klf2 , Dppa3 , Sox2 , Esrrb , Utf1 , Gbx2 , and Nr5a2 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…21 Normally, CpG dinucleotides are methylated in LINEs and other retrotransposable sequences to prevent their activation. 23 The results reflected that early changes in global DNA methylation probably occurred in tandem with increased in expression of de novo methyltransferases. 22 We have already shown that the methylation level of the CpG dyads for three classes of REs increased on the transition between the in vivo and in vitro pluripotent cell states.…”
Section: Introductionmentioning
confidence: 88%
“…The effects of unsilenced retrotransposons can be seen in cancer cells that have unstable genetic profiles. 23 To address the question of which regimen could better conserve genomic integrity during long-term passaging, in this study, the DNA methylation pattern of REs; their activation levels under 2i, R2i, and serum culture conditions; and the genomic integrity of cells were investigated. 23 The results reflected that early changes in global DNA methylation probably occurred in tandem with increased in expression of de novo methyltransferases.…”
Section: Introductionmentioning
confidence: 99%